Exploring the Broad Impact of AI Technologies on Student Engagement and Academic Performance in University Settings in Afghanistan - Fazil, Abdul Wajid; Hakimi, Musawer; Shahidzay, Amir Kror; Hasas, Ansarullah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2024)
This article explores the pivotal intersection of Artificial Intelligence (AI), student engagement, and academic performance in higher education, specifically at Kabul University. As technology evolves, understanding AI's implications on education becomes critical for effective pedagogical strategies and student readiness. The research aims to bridge the gap between technological advancements and educational practices, comprehensively investigating AI's impact on student engagement and academic performance. The study addresses awareness, ethical considerations, autonomy perceptions, and AI integration into curricula. Employing a quantitative approach, the study involves 200 students from various Kabul University faculties, utilizing SPSS version 23 for analysis. Regression analyses, ANOVA, and structured questionnaires allow a nuanced exploration of AI engagement dimensions. Key findings indicate commendable AI awareness in students' daily lives, with room for improvement in academic integration. Ethical considerations emphasize a baseline for ethical AI use. Autonomy perceptions and AI tool engagement reveal nuanced layers, emphasizing a holistic AI education approach. In conclusion, this research advocates a balanced AI integration in education, offering implications for pedagogical strategies, curriculum development, and institutional policies. The findings guide educators, policymakers, and institutions in navigating AI-enhanced learning environments, ensuring students' technological literacy and ethical grounding.